Race mixing : Black-white marriage in postwar America - Romano, Renee Christine (Harvard University Press, 2003)
"Marriage between blacks and whites is a long-standing and deeply ingrained taboo in American culture. On the eve of World War II, mixed-race marriage was illegal in most states, politicians argued for segregated facilities in order to prevent race mixing, and interracial couples risked public hostility, legal action, even violence. Yet sixty years later, black-white marriage is no longer illegal or a divisive political issue, and the number of such couples and their mixed-race children has risen dramatically. Renee Romano explains how and why such marriages have gained acceptance, and what this tells us about race relations in contemporary America." "Although significant numbers of both blacks and whites still oppose interracial marriage, larger historical forces have greatly diminished overt racism and shaped a new consciousness about mixed-race families. The social revolutions of the 1950s and 1960s (with their emphasis on individualism and nonconformity), the legal sanctions of new civil rights laws, and a decline in the institutional stability of marriage have all contributed to the growing tolerance for interracial relationships. Telling the powerful stories of couples who married across the color line, Romano shows how cultural shifts are lived by individuals, and how these shifts have enabled mixed couples to build supportive communities for themselves and their children." "However, Romano warns that the erosion of this taboo does not mean that racism no longer exists. The history of interracial marriage helps us understand the extent to which America has overcome its racist past, and how much further we must go to achieve meaningful racial equality."--Jacket